Genetic variations among selected wild Asian elephant populations in Peninsular Malaysia based on mitochondrial D-loop region DNA sequences - KAYAL VIZI KARUPPANNAN; NOR AIFAT RAHMAN; KHAIRUL AMIRIN MOHAMED; NURUL FARAH DIYANA AHMAD TAHIR; FATIN MARDHIAH NORDIN; SALMAH YAAKOP; JESÚS E MALDONADO; BADRUL MUNIR MD ZAIN (Society for Indonesian Biodiversity, 2019)
Abstract. Karuppannan KV, Aifat NR, Mohamed KA,  Ahmad-Tahir NFD,  Nordin FM, Yaakop S, Maldonado JE, Md-Zain BM. 2019. Genetic variations among selected wild Asian elephant populations in Peninsular Malaysia based on mitochondrial D-loop region DNA sequences. Biodiversitas 20: 2494-2502. Asian elephant (Elephas maximus) is an important large mammal in Peninsular Malaysia and is completely protected by the Wildlife Conservation Act 2010 (Act 716). The conservation of this species requires strong information-based research, such as genetic evaluations. The aim of this study was to compare mitochondrial control region variation among selected elephants from the Taman Negara National Parks (TNNP) population with other selected populations in Peninsular Malaysia. DNA materials were extracted from fecal samples and amplified using partial mitochondrial D-loop region. Total 13 haplotypes with haplotype diversity (Hd) of 0.7524 were observed. A total of 34 base pair (bp) segregation sites were formed in 547 bp sequences. Both phylogenetic trees showed that a few individual elephants from the TNNP formed a clade together with individuals from other populations. The remaining individual elephants from TNNP formed a monophyletic clade supported by a high bootstrap value. Low genetic distance was detected among the tested populations, which proved that both individuals from the TNNP and other selected populations have similar genetic patterns. High gene flow among tested populations would impact on fitness and long-term resilience of the populations. This highly significant outcome provides strong baseline data for Department of Wildlife and National Parks (DWNP) in monitoring elephant populations in order to reduce number of human-elephant conflicts which indirectly minimize translocating conflict elephants to TNNP.